1990
DOI: 10.1111/j.1476-5381.1990.tb14177.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of eicosanoids in PAF‐induced increases of the vascular permeability in rat airways

Abstract: 1 Platelet activating factor (PAF; 1.0 and 5.0,gkg 1) injected in the tail vein of unanaesthetized rats dose-dependently increased the vascular permeability of the trachea, upper and lower bronchi (up to 400%) as measured by the extravasation of Evans blue dye. The permeability of the parenchyma was not affected by PAF treatment. 2 Pretreatment of the animals with an intravenous injection of the PAF antagonist BN-52021 (10mgkg-1) abolished almost totally the vascular permeability changes elicited by PAF inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 15 publications
5
25
0
Order By: Relevance
“…In contrast, PAF-induced leakage was unaffected by all adrenaline pretreatments used. Our results are consistent with the failure of noradrenaline to attenuate significantly the airway leakage response to PAF in the rat (Sirois et al, 1990 (Bertram et al, 1983). Peripheral airways might be expected to account for a similar proportion of the total tissue volume in guineapig lung.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, PAF-induced leakage was unaffected by all adrenaline pretreatments used. Our results are consistent with the failure of noradrenaline to attenuate significantly the airway leakage response to PAF in the rat (Sirois et al, 1990 (Bertram et al, 1983). Peripheral airways might be expected to account for a similar proportion of the total tissue volume in guineapig lung.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, when higher doses of endothelin-1 (1 nmol kg-') and PAF (1.9 nmol kg-l) were injected simultaneously, markedly increased protein extravasation was detected in the airways, pancreas, duodenum and stomach. Interestingly, combined administration of endothelin-1 plus PAF evoked a significant increase in protein extravasation in the pulmonary parenchyma, where the classical inflammatory mediators fail to produce changes in macromolecular permeability (Maron, 1982;Grega et al, 1986;Sirois et al, 1990). The permeability effect of endothelin-1 was not affected by PAF in the spleen, whereas it was completely inhibited by PAF in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in rats, the vascular reactivity of the pulmonary vessels to complement activation contrasted with the sensitivity of the systemic vessels. Recently, Sirois et al (1990) reported that PAF increased vascular permeability in rat trachea and bronchi, as in other systemic vessels, but not in rat lungs. Our results agree with this observation.…”
Section: Discussionmentioning
confidence: 99%